A spontaneously healable robust ABA tri-block polyacrylate elastomer with a multiphase structure. Issue 40 (30th September 2021) - Wang, Wenyan; Guo, Zijian; Liu, Zongxu; Qiu, Shuai; Li, Chunmei; Zhang, Qiuyu
Abstract : Multiphase structural designed acrylate elastomer capable of autonomously repairing structures and restoring functions upon damage was developed via an effective method, realizing good mechanical properties. Abstract : Intrinsic self-healing elastomers capable of autonomously repairing structures and restoring functions upon damage have attracted significant attention. However, their mechanical properties tend to be poorer than those of similar common elastomers because of the low binding energies and poor interactions of dynamic motifs that confer good self-healing ability. The preparation of elastomers that combine autonomous self-healing ability and good mechanical properties remains challenging. In the present work, we have developed a facile and effective method to achieve mechanical toughening of polyacrylate elastomers by preparing an ABA tri-block copolymer without compromising self-healing performance using a multiphase design with different densities of physical crosslinks formed by carboxyl groups. An ABA tri-block acrylate copolymer with pre-designed A and B blocks was prepared via a two-step reversible addition–fragmentation chain transfer (RAFT) radical polymerization from commercially available monomers and subsequent acid hydrolysis. The resultant copolymer is transparent, and exhibits high fracture toughness (77.06 MJ m −3 ), high tensile strength (20.96 MPa) and good self-healing performance, with up to 93% of its original tensile strength and 83% of its original toughness after healing for 24 h at room temperature. This outstanding performance can be attributed to the novel multiple structural design, where the A blocks comprising polyacrylic acid (PAA) segments with high crosslink density maintain their macroscopic shape and provide the material with high mechanical strength, and the B blocks which are random copolymers of AA and n -butyl acrylate with sparse crosslinking dissipate energy to achieve exceptional mechanical toughening and enhance the mobility of molecular segments to promote autonomous self-healing ability via a dynamic breakage–recombination of hydrogen bonds. In addition, the as-prepared elastomer shows the characteristics of fluorescence emission, and exhibits shape memory behaviors.